INEQUITIES ANALYSIS IN LOCAL OWN-SOURCE REVENUE POTENTIAL BETWEEN REGENCIES AND MUNICIPALITIES IN INDONESIA - Zarkasi, Muhammad Ilham Husni; Khairi, Halilul; Wargadinata*, Ella Lesmanawaty (JWP (Jurnal Wacana Politik), 2024)
One of the underlying factors contributing to the low revenue of Local Own-Source Revenue (PAD) lies in the suboptimal utilization of PAD sources, notably stemming from shifts in economic structures, tax capacity, and imposed retributions. This study aims to analyze the inequality of PAD potential between regencies and municipalities, which results in the ratio of PAD to Local Government Budget (APBD) in regencies being significantly different from municipalities. This study aims to unveil the nuanced intricacies of PAD potential disparities by employing a mixed-method approach encompassing descriptive quantitative and qualitative analyses to capture comprehensive analysis. Data collected from scientific papers and secondary data which used content validation to control relevancy of different data sources. The results show that regency governments have different characteristics from municipal governments regarding geographical landscape, economic structures, and population. These differences affect the local revenue potential, which should be managed differently from municipal fiscal policy. The disparity in Public Agency Revenue (PAD) between the two entities is attributed to the national government’s failure to address the revenue-raising capabilities of regency governments adequately. Although local taxes are diverse, only a limited number are reliable local revenue sources. The field of taxation is characterized by a high degree of centralization, as the central authority collects all major and most productive types of taxes, including both direct and indirect taxes. The symmetric decentralization policy between regencies and cities progressively limits the capacity of district governments to enhance local revenue.